Immunological and Neurometabolite Changes Associated With Switch From Efavirenz to an Integrase Inhibitor. (15th August 2019) - Asundi, Archana; Robles, Yvonne; Starr, Tyler; Landay, Alan; Kinslow, Jennifer; Ladner, Joshua; White, Laura; Plank, Rebeca M.; Melbourne, Kathleen; Weisholtz, Daniel; Bennett, Monica; Pan, Hong; et al.
Abstract : Background: The biological mechanisms by which efavirenz (EFV) causes central nervous system (CNS) effects are unclear. The objective of this pilot study was to elucidate the mechanisms underlying these CNS effects by correlating well-described neuropsychological (NP) changes with neurometabolites and immunologic markers following switch off EFV. Setting: Two single-arm parallel switch studies among HIV-infected adults in Boston, USA, from 2015 to 2017. Methods: Twenty asymptomatic HIV-infected adults on EFV-containing regimens were switched to an integrase strand transfer inhibitor-based regimen for 8 weeks. NP assessments were conducted before and after switch and correlated with neurometabolite changes measured using magnetic resonance spectroscopy and immunological markers. All pre-EFV and post-EFV measures were evaluated using matched-paired analyses. Results: NP testing demonstrated improvement in the domains of mood, cognition, and sleep off EFV. Magnetic resonance spectroscopy revealed decreases in the neurometabolite glutathione level ( P = 0.03), a marker of oxidative stress after switch. Inhibitory neuronal activity as reflected by gamma-amino butyric acid levels increased ( P = 0.03), whereas excitatory neurotransmitters glutamine + glutamate (Glx) and aspartate decreased ( P = 0.04, 0.001). Switching off EFV was also associated with changes in inflammatory markers; plasma markers sCD14 ( P = 0.008) decreased, whereas I-FABP and TNFRI levels increased ( P = 0.05, 0.03). Cellular markers CD4 + and CD8 + HLA−DR−/CD38 + subsets both increased ( P = 0.05, 0.02). Conclusions: Even asymptomatic participants showed improvements in NP parameters when switched off EFV. These improvements were associated with decreased CNS oxidative stress and excitatory neuronal activity. Changes in immune activation biomarkers suggested overall decreased inflammation. EFV may exert CNS effects through oxidative and inflammatory pathways, providing insight into possible mechanisms of EFV neurotoxicity. Abstract : Supplemental Digital Content is Available in the Text.